A Capitalism for the People: Recapturing the Lost Genius of American Prosperity (an excerpt) - Luigi Zingales (Journal of Economic Sociology, 2015)
An economist at the University of Chicago, Luigi Zinagles, who was born in Italy, had a chance to observe for himself the negative consequences of high inflation and unemployment coupled with scandalous nepotism and clanship in his homeland. That experience deeply affected his professional interests. In 1988 Zingales moved to the USA, determined to prove that economists are supposed not only to explain the world but also to make it better. In his book “A Capitalism for the People” Zingales shows that American capitalism has been subjected to decay, resulting in the emergence of corrupt systems in Europe and many other countries. The American variety of capitalism developed under unique conditions of merit-based competition. Meritocratic competition contributed to an emerging trust in market and social mobility. However, this trust later was broken through the betrayal by those who were oriented to business elites, whose lobbyist groups began to affect how markets work. Intellectual classes kept silent when that betrayal happened. As a result, we have to choose between ‘redistribution populism’ and ‘business-oriented technocracy.’ However, Zingales suggests a solution associated with pro-market populism and the support of real free and open competition aimed at people’s prosperity and well-being, not aimed solely at serving the interests of large business. Zingales argues that the current situation has a lot in common with American populism in the late nineteenth century. Middle and lower classes have been getting poorer while higher classes have been getting richer. Economic reforms which may make the playing field more even could serve as a solution. Reforms that could be directed against business, primarily large business, actually will turn to be pro-market, according to Zinagles.Journal of Economic Sociology publishes the last chapter “Pro Market. Not Pro Business,” in which the author summarizes his conclusions and reviews the main ideas of the book.